LEGAL REVIEW OF CHILD NUTRITION HEALTH REGARDING THE CHALLENGES OF STUNTING IMPLICATIONS IN CHILDREN WITH SPECIAL NEEDS IN RURAL AREAS THROUGH THE UTILIZATION OF ARTIFICIAL INTELLIGENCE - Yulian, Ely (International Journal of Social Service and Research, 2024)
Children with special needs are vulnerable in rural areas to nutrition problems, including stunting, due to limited access to health services and minimal nutrition knowledge. Article 11 of Law No. 17 of 2023 on Health emphasizes the responsibility of the Central and Local Governments to provide access to healthcare facilities and health education. In this case, the utilization of artificial intelligence (AI) can help monitor, diagnose, and intervene more effectively against stunting through accurate data analysis and timely recommendations. The objective of this study is to analyse the legal challenges related to child nutritional health, especially stunting in children with special needs in rural areas, and explore the potential of utilizing AI in addressing this issue. The research method used is normative juridical, using a statutory approach and an analytical approach. The results show that children with special needs in rural areas face various challenges in accessing health services and nutritional information. Limited access, lack of community knowledge about the importance of nutrition, and lack of effective intervention programs are the main obstacles. On the other hand, the use of AI can help in early detection and treatment of stunting through health data analysis, and provide appropriate intervention recommendations. The use of artificial intelligence has great potential in improving the effectiveness of child nutrition health programs and reducing stunting cases among children with special needs in rural areas. Collaboration between the government, health institutions, and technology is needed to implement this solution effectively and sustainably.